Implementation : the 'Black Box' of school improvement. - Naidu, Divealoshani (My University, 2013)
The focus of this study was the challenge of implementing school improvement interventions from inception through the system to the school, within a framework of the multiple layers of South Africa's complex education system. These are the macro level, (the provincial and national political and bureaucratic decision makers), the meso-level (the role and function of district offices and external agents), and the micro level (local contexts at the site of the school). This study does not intend to evaluate school improvement interventions but rather to research and interrogate the mediation of the interventions at various levels and within the contextual realities of an education system in transition. The problem is three-pronged and is premised on understanding the link between the study of implementation and of school improvement within education in transition. The hypothesis put forward is that, on the one hand, contextual realties, contestation and contradictions at various levels of a complex organization shape the outcomes of a school improvement intervention. On the other hand, school improvement strategies must be further located within the framework of implementation in order to explore the complexities of getting things done in an emerging democracy. The challenge posed is whether a coherent link between implementation and school improvement can be achieved while taking into cognizance the three levels and the contextual realities informed by the legacy of the past. I identified two case studies of school improvement initiatives undertaken in the Gauteng province. The first was initiated during the first phase of the new democratic government, an EQUIP intervention programme initiated by the first Member of the Executive Council (MEC) for education in Gauteng. I chose EQUIP because the design and initiation of this intervention symbolized the political ideology of this first period of government. The second school improvement initiative, the Education Action Zone (EAZ) intervention, was chosen because it reflects a significant shift in political ideals in the second period of government. This study argues that school improvement in the emerging South African context must respond to the contested nature of transforming societies and the serious lack of cohesion and capacity at all levels of the system. In order to respond to this difficult terrain, implementation within a cyclic model must be an integral part of the design of a school improvement intervention. There must be a clear understanding of the political, cultural and technical nuances in each of the three environments. Implementation is dependent on actors in them, and the contextual realties shape the level of agency played by the people in each. The linkage also determines the fidelity, compliance, and communication of the message of the intervention as actors within each have different levels of power and authority to influence the change process.
Keywords: Implementation; School improvement; Reform intervention; Transformation